Demographics, higher investment and the future potential growth rate of the Irish economy - Paul Egan; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2024)
The Irish economy's recovery from the global financial crisis (GFC) has been striking with both economic output and the labour market registering significant increases in activity since 2013. This resurgence in performance followed the sharp decline witnessed in the economy during the period 2008 - 2012. Furthermore, it drew comparisons with the earlier growth observed during the ''Celtic tiger'' period. However, the recovery in the economy has coincided with acknowledged deficits in both social and physical infrastructure. A legacy of the post GFC crash has been a fall-off in investment rates in the Irish economy. This comes at a time when there has been an unexpected increase in recent population levels. We use a standard Solow growth model framework to decompose the past performance of the Irish economy over the period 1995 - 2023. We then parameterise the model to generate long-run forecasts for the domestic economy under a baseline and alternative scenarios related to population growth and rates of investment. The paper finds that increasing investment rates, even to rates below those at the peak of the Celtic Tiger era, would result in output growth increasing by up to 0.9 per cent per annum above the baseline rate.
Keywords: 330; Bevölkerungsentwicklung; Investition; Wirtschaftswachstum; Wirtschaftsprognose; Irland